2010
DOI: 10.2215/cjn.04030609
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea Is Associated with Cardiovascular Risk Factors among Kidney Transplant Patients

Abstract: Background and objectives:We assessed the prevalence of obstructive sleep apnea (OSA) and its clinical correlates in a large sample of patients who received a kidney transplant (Tx). We also compared the prevalence of the disorder between dialysis patients who were on the waiting list for a Tx (WL) and Tx patients. Conclusions: The prevalence of OSA is similar in Tx and WL patients and it may contribute to presence of hypertension in patients who receive a Tx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 35 publications
(31 reference statements)
3
23
0
6
Order By: Relevance
“…[28][29][30][31][32][33][34] Potentially eligible patients were selected from all prevalent adult kTx recipients (total clinic population; n = 1,214) who were regularly followed at a single outpatient academic transplant center, the kidney transplant clinic of the Department of Transplantation and Surgery at the Semmelweis University, Budapest, Hungary (Figure 1). All patients followed at the clinic on December 31, 2006 were considered for enrollment in the Malnutrition and INflammation In Transplant (MINIT-HU) study.…”
Section: Sample Of Patients and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30][31][32][33][34] Potentially eligible patients were selected from all prevalent adult kTx recipients (total clinic population; n = 1,214) who were regularly followed at a single outpatient academic transplant center, the kidney transplant clinic of the Department of Transplantation and Surgery at the Semmelweis University, Budapest, Hungary (Figure 1). All patients followed at the clinic on December 31, 2006 were considered for enrollment in the Malnutrition and INflammation In Transplant (MINIT-HU) study.…”
Section: Sample Of Patients and Data Collectionmentioning
confidence: 99%
“…The creation of the cohort has been described previously. [28][29][30][31][32][33][34] From these 150 eligible patients, 100 individuals agreed to participate and they underwent 1-night PSG (kTx participant sample). From this sample of 100 patients, 3 were excluded from our analysis because of a missing depression score and 2 were excluded because of antidepressant pharmacotherapy.…”
mentioning
confidence: 99%
“…The complex pathophysiology that links OSA to cardiovascular risk may also have a detrimental effect on kidney function. Patients with OSA experience glomerular hyperfiltration, which is alleviated by short-term CPAP treatment,13 but our previous studies in kidney transplant recipients found no association between OSA and deterioration of kidney function 14 15. Only one recently published study assessed the association of OSA with kidney function decline and progression to CKD in non-transplant patients 16…”
Section: Introductionmentioning
confidence: 99%
“…In previous surgical studies, OSA patients were more likely to have several common comorbidities including cardiac and vascular disease, hypertension 15-20 , congestive heart failure and stroke 17,18 ; dyslipidemia 17 and diabetes 17 than the general population. Most of these comorbidities are related to obesity 17-19,21 and associated with increased risk of perioperative and postoperative complications 22 .…”
Section: Introductionmentioning
confidence: 99%